Ethics, issues and challenges in quality global Online Distance Higher Education provision - Angelo Nicolaides; Joseph Mensah Onumah (West African Journal of Open and Flexible Learning, 2017)
The quest for quality in the learning process in Open Distance Higher Education (ODeL) is enduring and it is hopefully persistently leading to better ways which would enable quality learning to take place. It is apparent that many distance education institutions are moving from a purely print-based to an online delivery approach through the use of virtual learning environments (VLEs) and by making use of numerous technological innovations. Academic institutions are challenged to prepare graduates to compete ethically in the 21st Century knowledge economy. In some ways however, technology is somewhat of a disruptive innovation. This paper discusses the issues and challenges that online distance higher education (ODeL) poses and discusses strategies which could possibly be employed by institutions to diminish unethical practices and further suggests some reasons why students choose to be dishonest in the digital era. It is clear that policy development and administrative changes are required to support innovative teaching practices across an institution. Distance education (DE) is also progressively global, with universities leveraging cutting 22 West African Journal of Open & Flexible Learning Volume 5, Number 2, January 2017 edge technologies to place education within the grasp of many more individuals and this requires additional skills. Suggestions are also proffered as to what academics can do to mitigate unethical academic practices. In this regard, a carefully crafted moral education approach and well-conceived course design are needed to construct a sound academic culture and promote the desired levels of integrity. The core issue is how unethical student practices can be eliminated where the use of information technology is required in all teaching and learning. The findings and conclusions may be relevant for other institutions in the ODeL arena.